POLITICAL SECTARIANISM IN IRAQ 1921-1958 - Assist Prof. Dr. Fatima Hosein Saloumi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Our research entitled (Political Sectarianism in Iraq 1921-1958) summarizes the first historical roots of sectarianism in Iraq by explaining its problems, linguistic and idiomatic concepts, and how it emerged from the Ottoman and British occupation until the beginning of the republican rule in 1958 and past its jurisprudence of political variables that were linked to the specificity of Iraqi society and its internal challenges. And foreign affairs under the rule of the military, which was one of the pillars of the political system and the structure of the state in Iraq in terms of political practice that characterizes individuals in belief and sect, as well as all the rights and duties that everyone enjoys, especially since social identity in all its subtypes, national, ethnic, religious and family types is A necessity and an inevitable product of the individual’s desire to belong to a social entity, from which he derives security, status and respect, because society in general represents a social fabric with many components and sects, since the establishment of the Iraqi state in 1921 and the announcement of its formation as a modern state with multiple social and economic potentials despite the negative effects of the Ottoman and British occupiers, which formed a factor A weakness of the emerging Iraqi identity.